Topographical Effects on Volcano Deformation Signal Intensity: Implications for GPS Network Configuration - J. Hickey; K. Pascal; R. Syers; R. Alshembari (Geophysical Research Letters)
Abstract Volcano GPS networks can capture vital information during volcanic unrest to aid with hazard assessment and eruption forecasting, but can be hindered by their discrete point locations and possibly miss key spatial information. We show how numerical models can reveal controls on spatial deformation signal intensity compared against GPS network design. Using the GPS network at Soufrière Hills Volcano (SHV), Montserrat, and a range of models, we explore expected surface deformation patterns. Peak horizontal deformation is located offshore, highlighting the difficulties with geodetic monitoring on small ocean‐island volcanoes. Onshore areas where the deformation signal is expected to be high are also identified. At SHV, topography plays a greater role in altering the relative distribution of surface displacement patterns than subsurface heterogeneity. Our method, which can be adapted for other volcanoes, highlights spatial areas that can be targeted for effective GPS station placement to help improve deformation monitoring efficiency.